Financial deregulation, financial system development and economic growth in Mexico: Long-term effects and causation - Venegas Martínez, Francisco; Tinoco Zermeño, Miguel Ángel; Torres Preciado, Víctor Hugo (Estudios Económicos de El Colegio de México, 2009)
Specialized literature states that a deregulated financial system has positive effects on long-term economic growth. The Mexican financial system has gone through two major phases: regulation until 1988 and soon after liberalization. In this framework, by using cointegration and causality tests the effects of financial repression and financial intermediation on economic growth are examined.